Convenient New Bedside and Laboratory Method for the Control of Anticoagulant Therapy - Hartert, H (Thrombosis and Haemostasis, 1962)
A new simple method is described for the determination of thromboplastin time on 0.02 ml of capillary blood. It employs an automatic pipette with a disposable mouthpiece (sections of a plastic capillary tube), which is replaced by a new one after each determination. The automatic pipette may be used in the same way for pipetting the thromboplastin suspension into the test tube. The latter is the only utensil, which has to be cleaned after the determination.In comparison with other procedures of thromboplastin time determinations, the new micro-method has been found as reliable as “macro”-methods using venous blood.